Current issues in Islamic banking and finance : resilience and stability in the present system - Venardos, Angelo M. (World Scientific, 2010)
"The phenomenal worldwide development over the past decade of Islamic banking and finance is drawing much attention to Southeast Asia, which, on the platform of its own economic growth success, is also proving to be the gateway for Middle Eastern petrodollar investments into the two great emerging markets of India and China. This book provides a timely examination of the issues confronting this US$300 - US$500 billion market growing at 15% - 20% per annum, with reviews of the different financial markets, be they capital (Sukuk), retail or wealth management. It further includes reviews from the various jurisdictions including Malaysia (the front-runner), Singapore (the regional financial hub), Brunei (an offshore Islamic market player) and the sleeping giant, Indonesia, as well as newly emerging participants such as Japan and the United States. Contributors, all well-known leading practitioners in their fields, range from lawyers, accountants, bankers and educators to policy advisors, and come from institutions such as CIMB, Kuwait Finance House, OCBC Bank and PricewaterhouseCoopers, among others." -- Book cover.